1997
DOI: 10.1046/j.1537-2995.1997.37597293874.x
|View full text |Cite
|
Sign up to set email alerts
|

A point score system for predicting the likelihood of blood transfusion after hip or knee arthroplasty

Abstract: The likelihood of a postoperative blood transfusion can be predicted by using this simple point score system. Autologous blood donation can subsequently be targeted to the high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 22 publications
1
25
0
5
Order By: Relevance
“…A recent report from Canada found that only 4% of patients undergoing unilateral knee arthroplasty required allogeneic transfusion, whereas 31% of patients undergoing bilateral knee arthroplasty received allogeneic blood [31]. This report and our current study supports a conclusion that autologous blood procurement is not necessary for patients undergoing initial, unilateral knee arthroplasty.…”
Section: Discussionsupporting
confidence: 89%
“…A recent report from Canada found that only 4% of patients undergoing unilateral knee arthroplasty required allogeneic transfusion, whereas 31% of patients undergoing bilateral knee arthroplasty received allogeneic blood [31]. This report and our current study supports a conclusion that autologous blood procurement is not necessary for patients undergoing initial, unilateral knee arthroplasty.…”
Section: Discussionsupporting
confidence: 89%
“…24 These data suggest that a perioperative bleeding event should not increase the risk of death unless the hemoglobin level goes below 80 g/L or perhaps 70 g/L. Finally, numerous investiga- tors have attempted to predict bleeding requiring perioperative blood transfusion in noncardiac surgery, [25][26][27][28][29][30][31] but those studies were small compared to our study, with samples ranging from 94 to 1875 patients, and were often limited to a single centre and type of surgery.…”
Section: Discussionmentioning
confidence: 71%
“…Tranexamic acid has been shown to effectively decrease blood loss and postoperative transfusion rates in orthopedic patients without an increase in TEE [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Other studies investigating risk factors for postoperative transfusion found preoperative Hgb to be a significant predictor for subsequent packed red blood cell transfusion [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these investigations demonstrated preoperative Hgb value to be a significant predictor of postoperative transfusion [23][24][25][26]. As such, there are certain preoperative Hgb levels where postoperative transfusion is less likely and the utility of TXA is unknown.…”
mentioning
confidence: 99%